A MODIFIED NEOCLASSICAL GROWTH MODEL WITH ENDOGENOUS LABOR PARTICIPATION - Delano Segundo Villanueva (Bulletin Ekonomi Moneter dan Perbankan, 2020)
In light of robust econometric results on the determinants of labor participation in 36 advanced economies reported by Grigoli et al. (2018) and independently by CBO (2018), my paper modifies the Solow (1956) - Swan (1956), or S-S, growth model by making endogenous the rate of labor participation (exogenously fixed at a constant fraction of population in the S-S model). By allowing a fully adjusting natural rate, I find that the positive growth effects of a higher saving rate hold in the transition to and in the steady state (a generalization of the S-S model).